Fetal Isolated Anomalous Origin of Right Pulmonary Artery from Aorta - Shi Zeng; Qichang Zhou; Jiawei Zhou; Qinghai Peng (Thieme Medical Publishers, Inc., 2015)
Abstract The anomalous origin of a branch pulmonary artery from the aorta (AOPA) is characterized by the anomalous origin of one of the branch pulmonary arteries (PA) from the ascending aorta and a normal origin of the other PA from main PA. AOPA is an extremely rare cardiac malformation. Few studies have reported fetal anomalous origin of PA from aorta with other malformation. We report a case of isolated distal anomalous origin of the right PA from the aorta that was diagnosed by fetal echocardiography at 25 weeks' of gestation. Tracing the course of PA branches is important to make diagnosis.